Subjective Sleep Quality and Daytime Sleepiness Among Greek Nursing Staff: A Multicenter Cross-Sectional Study - Mantzanas, Michalis; Chrysikos, Dimosthenis; Giannakodimos, Ilias; Chelidonis, George; Drymousi, Paraskevi; Pechlivanidou, Evmorfia; Pikoulis, Emmanouil; Basios, Neofytos; Zografos, Contantinos G.; Zografos, George C.; Karavokyros, Ioannis (Health & Research Journal, 2022)
Background: Lack of sleep and sleep of poor quality contribute to fatigue, decreased productivity, increased risk of accidents and errors at work. Aim: The aim of the current study is to further investigate the relationship between sleep quality and daytime sleepiness to demographic and work environment characteristics among the nursing stuff. Method and Material:A cross-sectional study was performed on nursing staff, in Athens, from July 2018 to June 2020 focused on characteristics related to poor sleep and sleep disturbance. Results: This cohort investigated 70% poor sleep and 25% excessive daytime sleepiness among nursing staff. Sleep disturbance was related to young age and serving as a ward nurse. Personal as well as departmental and institutional factors affected sleep quality but not excessive daytime sleepiness. Conclusion: Health system managers and nurse leaders should take under consideration not only personal, but also departmental and institutional characteristics when taking support measures to maintain nurses' mental health and patient’s safety.